METABOLIC CHANGES INDUCED BY BUSHENHUOXUE GRANULES ON STRIATUM AND SUBSTANTIA NIGRA IN A RAT MODEL OF PARKINSON’S DISEASE - Guo, Yunxia; Zhang, Junxiu; Li, Shaodan; Zhang, Yin; Liu, Yi; Yang, Minghui (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Parkinson’s disease is a neurodegenerative disease, while its mechanism is still unclear. Long-term levodopa-based treatment leads to decreased response or loss of response, as well as severe side effects. Our previous study has proved that Bushenhuoxue Granules have effects on Parkinson’s disease, but the underlying mechanism is still need to be explored. Our research is to investigate the mechanisms of Bushenhuoxue Granules on Parkinson’s disease (PD) by examining changes in the expression of the adenosine A2A receptor、vesicular monoamine transporter 2 (VMAT2)、divalent metal transporter 1(DMT1) and nuclear factor E2 related (Nrf2) in a rat model of Parkinson’s disease (PD) . Materials and Methods: Changes in the apomorphine (APO)-induced rotational behavior of rats were observed after treatment. Immunofluorescence and immunohistochemistry were performed to investigate changes in adenosine A2A receptor 、VMAT2、DMT1 and Nrf2 expression in the rat striatum and substantia nigra. Results: Rotations after treatment were199.11 ± 27.16, which significantly decreased compared with that before treatment ( 273.0 ± 44.61, p < 0.01). Adenosine A2A receptor expression in the striatum was 3.10 ± 0.34 significantly increased in the model group and decreased in the normal control group, whereas the expression level in the Bushenhuoxue group was 1.13 ± 0.23,p < 0.05 between the two control groups. No adenosine A2A receptor expression was observed in the substantia nigra. VMAT2 expression in the rat striatum was 23.20 ± 2.68 and substantia nigra was 15.98 ± 0.70 increased in the normal control group. They were 8.99 ± 0.48 in the rat striatum and 8.45 ± 0.59 substantia nigra significantly decreased in the model control group, whereas the expression level in the Bushenhuoxue group was 15.36 ± 0.89 in the rat striatum and 11.69 ± 1.17 in the rat substantia nigra (p < 0.05), also between the two control groups. DMT1 expression in the rat striatum was 3.30 ± 0.30 and substantia nigra was 6.56 ± 0.64 decreased in the normal control group. They were 7.92 ± 0.52 in the rat striatum and 12.76 ± 0.86 substantia nigra significantly increased in the model control group, whereas the expression level in the Bushenhuoxue group was 6.17 ± 0.27 in the rat striatum and 9.13 ± 0.44 in the rat substantia nigra (p < 0.05), also between the two control groups. Nrf2 expression in the rat striatum was 7.90 ± 0.29 and substantia nigra was 15.22 ± 1.22 increased in the normal control group. They were 3.09 ± 0.43 in the rat striatum and 8.57 ± 0.54 substantia nigra significantly decreased in the model control group, whereas the expression level in the Bushenhuoxue group was 5.00 ± 0.34 in the rat striatum and 12.46 ± 0.62 in the rat substantia nigra (p< 0.05), also between the two control groups. Conclusion: Bushenhuoxue Granules significantly improved the rotational behavior of PD’s rats, decreased adenosine A2A receptor expression, and increased VMAT2 expression; decreased DMT1 expression, and increased Nfr2 expression.